2013
DOI: 10.1590/s0104-07072013000300012
|View full text |Cite
|
Sign up to set email alerts
|

Fatores desencadeantes do uso de drogas de abuso em mulheres

Abstract: O objetivo deste estudo foi identificar e discutir fatores desencadeantes do uso de drogas em mulheres. Estudo qualitativo de caráter descritivo com 12 mulheres provenientes de três municípios do Paraná, notificadas a um centro de assistência toxicológica nos anos 2008 a 2010. Os dados foram coletados da ficha de Ocorrência Toxicológica dos prontuários, e do roteiro para entrevista semiestruturado aplicado durante visita domiciliar e analisados por conteúdo temático. A maioria era da raça/cor parda, estava ent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
19
0
44

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(66 citation statements)
references
References 12 publications
3
19
0
44
Order By: Relevance
“…As for the socioeconomic characteristics of the interviewees in this study, there was congruence with the results of other studies of women who were treated at UBS, demonstrating that they are, mostly, young, married, with monthly income around one minimum wage and that they make use of cigarettes and alcohol, preferably [9,10,13].…”
Section: Discussionsupporting
confidence: 84%
See 3 more Smart Citations
“…As for the socioeconomic characteristics of the interviewees in this study, there was congruence with the results of other studies of women who were treated at UBS, demonstrating that they are, mostly, young, married, with monthly income around one minimum wage and that they make use of cigarettes and alcohol, preferably [9,10,13].…”
Section: Discussionsupporting
confidence: 84%
“…Similar data were found in a study of women who sought care in a Psychosocial Care service in the city of Teresina-PI, being most participants 19 years old (53.4%) [9]. Another survey conducted in three municipalities of the Paraná State showed that 12 SPA users interviewed were aged between 17 and 33 years [10].…”
Section: Discussionsupporting
confidence: 78%
See 2 more Smart Citations
“…Nessa perspectiva, entende-se a ideia dos familiares das participantes deste estudo de que o consumo de crack foi causado pelas "más companhias", uma vez que o companheiro e suas interações sociais são importantes fatores de risco para o uso de drogas. Além disso, a literatura evidencia o grupo familiar, quando constituí-do de integrantes usuários de drogas, como fator de risco para o retorno do uso de crack após o tratamento (Marangoni & Oliveira, 2013;Seleghim & Oliveira, 2013). Assim, é importante considerar o ambiente e o contexto social ao qual a usuária retornará após o tratamento, abrangendo aspectos que a auxiliem na manutenção do propósito buscado no tratamento, diminuindo os problemas relacionados ao uso de crack.…”
Section: Discussionunclassified